DINAMIKA MASYARAKAT DAN KEBUDAYAAN TERHADAP PENDIDIKAN - Alfina; Puspitasari, Elvi; Salimu, Salman Alfarisi (Universitas Aisyah Pringsewu, 2025)
The dynamics of society and culture have an influence on the development of education systems in the world. Changes in social structures, cultural values, and technological advances can influence aspects of education, from the curriculum, learning methods, to the goals of education itself. This article aims to analyze the impact of changing societal and cultural dynamics on education, with a focus on how these factors shape perspectives on education, the relevance of the curriculum, and the development of students' skills and character. Apart from that, this article also discusses the challenges faced by the education system in responding to changes in culture and society, such as the need for multicultural education, adaptation to technological advances, and increasing awareness of diversity. With an analytical approach, this article provides insight into the importance of integrating social and cultural dynamics in designing an education system that is more responsive, inclusive and relevant to the needs of the times. It is hoped that the findings in this analysis can contribute to the development of education policy.